Pengembangan model pembelajaran simplified problem based learning materi Surah Al Fatihah dan Al Ikhlas mata pelajaran Pendidikan Agama Islam kelas IV di SDN Kranggan 3 Kota Mojokerto - Cahyo, Hariris Nur (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
Problem Based Learning Model is an innovation in learning because in this model students' thinking ability is optimized through a systematic group or team work process, so that students can empower, sharpen, test, and develop their thinking ability on an ongoing basis. However, not all educators (teachers) understand the concept of the Problem Based Learning Model. The purpose of this research development is: 1) To determine the feasibility of learning model simplified problem based learning material Surah Al Fatihah and Al Ikhlas subjects Islamic Religious Education class IV SDN Kranggan 3 Kota Mojokerto according to Expert. 2) To know the feasibility of learning model simplified problem based learning material Surah Al Fatihah and Al Ikhlas subjects Islamic Religious Education fourth grade SDN Kranggan 3 City Mojokerto according to peers 3) To know the interest of learning model simplified problem based learning material Surah Al Fatihah and Al Ikhlas subjects Islamic Religious Education class IV SDN Kranggan 3 Kota Mojokerto according to student ratings. The selection and use of learning model based on simplified problem based learning can effectively streamline and streamline the implementation of learning. For that purpose, the learning model based on simplified problem based learning is absolutely necessary. Learning Products Islamic Education Learning model based learning simplified problem based learning has been refined based on analysis of test data. Based on the steps that have been implemented can be concluded as follows. 1) The learning model of simplified problem based learning of Surah Al Fatihah and Al Ikhlas subjects of Islamic Religious Education grade IV SDN Kranggan 3 Kota Mojokerto feasible according to Expert 2) Learning model of simplified problem based learning material Surah Al Fatihah and Al Ikhlas subjects Islamic Religious Education Class IV SDN Kranggan 3 Mojokerto city feasible according to peers 3) Learning model simplified problem based learning material Surah Al Fatihah and Al Ikhlas subjects Islamic Religious Education grade IV SDN Kranggan 3 Kota Mojokerto interesting according to student ratings